2020
DOI: 10.7759/cureus.11893
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year-Old with Frequent, Disruptive, and Unexplained Night Awakenings

Abstract: A 10-year-old female presented to the sleep clinic for a second opinion about her epilepsy diagnosis. She had been treated with antiepileptic medication but her events persisted. The child would wake up several times every night speaking nonsense words, appear confused to her family, and then go back to sleep. A video of the polysomnography (PSG) showed the patient having two of her typical events. The patient was eventually diagnosed with confusional arousal (CoA) secondary to obstructive sleep apnea (OSA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Epileptiform abnormalities, rhythmic slow activity, or diffuse background flattening over frontal areas are seen in 50-60% of cases. A large cohort study reported a diagnostic delay of 12.8±10.1 years in 53.7% of SHE cases, with parasomnias being the most frequent misdiagnosis (55.5%) [1]. It is essential to recognize the clinical cues that would raise concerns for an underlying seizure disorder like SHE to provide an early referral to the consultant.…”
Section: Introductionmentioning
confidence: 99%
“…Epileptiform abnormalities, rhythmic slow activity, or diffuse background flattening over frontal areas are seen in 50-60% of cases. A large cohort study reported a diagnostic delay of 12.8±10.1 years in 53.7% of SHE cases, with parasomnias being the most frequent misdiagnosis (55.5%) [1]. It is essential to recognize the clinical cues that would raise concerns for an underlying seizure disorder like SHE to provide an early referral to the consultant.…”
Section: Introductionmentioning
confidence: 99%